Tool use in urban populations of capuchin monkeys Sapajus spp. (Primates: Cebidae) - Lucas M. Aguiar; Raphael M. Cardoso; Janaína P. Back; Eduarda C. Carneiro; Adriane Suzin; Eduardo B. Ottoni (Zoologia (Curitiba), 2014)
Capuchin monkeys, Sapajus Kerr, 1792, are known for their flexible behavior, including tool use, and their ability to survive in urban forests. We observed capuchin juveniles using wood as hammer and anvil and different materials as sponges (four tool-use events) in two geographically distinct urban populations in Brazil, in 2012: two in Goiânia, Central Brazil and two in Foz do Iguaçu, Southern Brazil. In Goiânia, a male used a detached tree branch as a hammer and a buttress root as an anvil to pound a seed of Terminalia Linnaeus. Another male used a small branch with leaves as a dipping tool to access water inside a tree trunk hole. In Foz do Iguaçu, the capuchins used a small branch and a piece of bread to obtain water by dipping them into tree trunk holes. This latter event might be interpreted as a case of self-control, with a familiar food item used as a tool to reach a resource that is difficult to access otherwise. Our observations contribute to the knowledge on the tool-kit of capuchins and we propose that these urban populations should be conserved for scientific evaluations of behavioral flexibility in non-human primates.